The Legal Framework for Carbon Trading: Examining its Juridical Implications for Civil Liability and Environmental Responsibility in Indonesia - Rahmawati, Diah Ayu; Haryono, Haryono; Endarto, Budi; Soraya, Joice; Santoso, Bagus Teguh (Westscience Press, 2025)
The Indonesian legislation on carbon trading is a key instrument for national and global climate targets. This analysis, according to the present study, utilizes a normative juridical model in viewing Indonesia's carbon trading law and focusing on implications toward civil liability and environmental obligation. The findings suggest that while the model is aligned with international norms and is multi-carbon price inclusive, it is beset with enforcement uncertainties, uncemented provisions of civil liability, and weakly constructed monitoring mechanisms. Additionally, the absence of adequate community participation mechanisms is not only an issue of equity and social inclusion. In learning from global best practices, such as the European Union Emissions Trading System (EU ETS) and China's national carbon market, the research identifies areas of improvement that involve enhancing legal clarity, enforcement mechanisms, and environmental responsibility. These are key in ensuring that Indonesia's carbon trading system has a sufficient contribution to promote both legal accountability and environmental sustainability.